2018
DOI: 10.1177/1359105318814152
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the causes of breast cancer treatment delays at a teaching hospital in Ghana

Abstract: Poor outcome for breast cancer in Ghana have been attributed to late presentation of symptoms at biomedical facilities. This study explored factors accounting for delays in initiation of breast cancer treatment at the Korle-Bu Teaching Hospital in Accra. Focus group discussions were conducted with twenty women with breast cancer. A theory-driven thematic analysis identified three multilevel factors influencing treatment seeking delays: (1) patient (e.g misinterpretation of symptoms, fear); (2) healthcare provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 24 publications
1
42
0
5
Order By: Relevance
“…With these financial challenges faced by these women, they had to rely on family members, employers and other people for assistance to enable them go through treatment. A lot of studies have reported similar findings (Sanuade et al, 2018;Twahir et al, 2019;White-Means, Dapremont, Davis, & Thompson, 2020). Amid the financial difficulties, some employers promised to assist some participants with payment of hospital bills;…”
Section: Discussionmentioning
confidence: 89%
“…With these financial challenges faced by these women, they had to rely on family members, employers and other people for assistance to enable them go through treatment. A lot of studies have reported similar findings (Sanuade et al, 2018;Twahir et al, 2019;White-Means, Dapremont, Davis, & Thompson, 2020). Amid the financial difficulties, some employers promised to assist some participants with payment of hospital bills;…”
Section: Discussionmentioning
confidence: 89%
“…Logistical di culties included different waiting times for an appointment (medical or specialist consultation), investigations (imaging, biopsy), test results, referral or treatment (surgery, radiotherapy) [23][24][25][26][27][28][29][30][31]. A long waiting time for test results, more speci cally for the biopsy results, was a factor in uencing the time to treatment in 11 included studies [24,[26][27][28][29][30][32][33][34][35][36]. Seven included studies reported that referral was delayed for women who had visited other health facilities 1 to 4 times or more before visiting the diagnostic centre [23,24,30,[36][37][38][39].…”
Section: Health Service Deliverymentioning
confidence: 99%
“…The geographical inaccessibility of healthcare facilities and the insu ciency of diagnostic centres are part of the infrastructure problems [28][29][30][31]41]. In Uganda, for instance, one patient interviewed said, 'The health centre nearby the community does not offer screening services, and someone may nd it hard to leave this place [Ssisa sub-county] to go to Kampala; but if they bring the services closer to the community, some will nd it easier to visit them.'…”
Section: Health Service Deliverymentioning
confidence: 99%
See 2 more Smart Citations